prevalence and causality assessment of adverse drug reaction among outpatients taking antiepileptic drugs in a tertiary care center of Nepal. - Guragain, Neha (2021)
ABSTRACT: Background Adverse drug reactions (ADRs) are the rising cause of morbidity and mortality, and rank among top ten causing mortality. Antiepileptic drugs (AEDs) are frequently associated with various adverse drug reaction which carry burden and treatment challenges. Epilepsy patient have long duration of antiepileptics therapy causing many adverse effects such as cognitive behavior, metabolic, hematological disorders and also has frequent drug interactions. There are limited studies in Nepal focusing on ADRs with AEDs in outpatient settings. Objective The objective of this study was to assess the prevalence and Causality assessment of ADRs among the patients under antiepileptics drugs presenting to Neurology OPD of Tribhuvan University Teaching Hospital of Nepal Methods A prospective longitudinal observational study was conducted for one year from March 2020 to Feb 2021 in the 'Neurology out-patient Clinic under the Department of Neurology at Tribhuvan University Teaching Hospital. All new and old cases (n=130) with the diagnosis of epilepsy who were on antiepileptics therapy, and met the inclusion criteria during the study period and had given written consent were enrolled, in our study. All data were recorded in a predesigned proforma sheet and descriptive statistical analysis was done by using Statistical Package for Social Sciences (SPSS), version 20. ADR causality was assessed using the Naranjo algorithms. Chi- square test was used in contingency tables and a p-value with a significance level of <0.05 was be used. Descriptive statistics were used to calculate percentages frequencies. Result A total of 130 patients with epilepsy were included in the study period. Among them, 57.7% were male. The mean age of study population was 33.5514.41 years. Majority of the epileptic patients were affected with generalized seizure 66.2% followed by patients affected with focal seizure 33.8%. Most of the participants were being treated with an AED monotherapy 53.84%. Levetiracetam 31.53% was the most prescribed drug in monotherapy followed by Sodium Valproate 12.3%. Most prescribed AEDs combination in polytherapy was Levetiracetam and Clobazam 15.38%, followed by Sodium Valproate and Levetiracetam 7.69%. A total of 31.53% patients had 109 different ADRs. The commonest ADR affecting organ system were central nervous system (CNS) in 86.3%. Among CNS, dizziness was seen in 36.69% patients followed by somnolence in 18 (16.51%). ADRs with AEDs polytherapy were found in 58.5% patients and with monotherapy in 41.4%. There was no any significant difference in ADRs frequency between monotherapy and polytherapy (P valve =0.055). According to Naranjo causality assessment scale, 54.4% patients were grouped in possible and 45.6% in probable. Conclusion The present study has provided data on prevalence of ADRs among outpatients taking antiepileptics patient. The current results showed different ADRs involving in organ system and with AEDs regimen. Our study shows that majority of the ADRs were from CNs manifestation. In our study higher proportion of receiving polytherapy presented with ADRs as compared to those receiving monotherapy. Majority of the ADRs were found to be possible followed by probable on Naranjo causality assessment scale remained unreported due to the lack of healthcare professionals understandings, interests or the skills needed to recognize and report them. The findings of our study highlights the importance of regular monitoring and reporting of ADRs. Keywords Adverse drug reactions, Causality, Pharmacovigilance, Polytherapy, Epilepsy